Pengaruh Budaya Organisasi dan Gaya Kepemimpinan terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening - Hawik Ervina Indiworo (STIE Widya Manggala, 2009)
The purpose of this paper is to analyst the influence of corporate culture and leadership style toward job satification to enhance employee performance. Using these variables, for instance Bass dan Avoliso, (1993); Tierney et al., (1999), Lund, (2003), Chen (2004), dan Nahar, (2004), discovered effect corporate culture and leadership style toward job satisfication to increase employee’s performance. The study was conducted at PT. Bank Bukopin Semarang Branches, the sample size is about 141 employee, using the Structural Equation Modelling (SEM). The results show that corporate culture and leadership style has positive significance effect on job satification is 0,47; The effect of corporate culture on job satification is 0,41; The effect of leadership style on employee performance is 0,27; The effect of corporate culture style on employee performance is 0,31; and the effect of organizational commitment on employee performance is 0,26.